THE ROLE OF POSITRON-EMISSION TOMOGRAPHY IN DIAGNOSIS OF EYE CANCER OF THE ORGAN OF VISION - D. A. Vazhenina; I. Е. Panova (Сибирский онкологический журнал, 2016)
The experience of application of positron-emission tomography in diagnosis of eye cancer has been described.